Analysis of Corporate Financial Decisions at PT Telekomunikasi Indonesia Tbk in Order to Increase Its Firm Value - Whuana, Wiweka Reksa; Soekarno, Subiakto (The Indonesian Journal of Business Administration, 2014)
Abstract— Any firm goes through the same life cycle – start up, rapid expansion, high growth, mature growth and decline. There are similar characteristics shared by firms within the same phase of life cycle in term of choices to increase firm value. They also typically share the same financial performances although some firm may not face the same circumstances. But it is rather an exception than the norm. PT Telekomunikasi Indonesia, Tbk (Telkom) has seen its growth decelerating. While on the other hand, it wishes to achieve market capitalization ofIDR 300 trillion by 2015. This paper analyzes corporate finance decisions of Telkom in its bid to increase the stock price. This study also employ the concept of corporate finance as outlined by Damodaran (2010), in which corporate finance can be detailed into three important decisions: investment, financing and dividend decision. This study found the investment decision, represented by IDN, to be feasible from the valuation standpoint. However, it is subject to Telkom satisfying several assumptions. The capital structure of Telkom is also found to be optimal, in the sense that the cost of capital is the lowest. On dividend front, this study concluded that Telkom still has more cash to be returned to the shareholders.The implementation of IDN should be done in an orchestrated and well-planned manner. Units responsible for deploying the capital expenditure should keep up with the schedule. Any late deployment will impact the ability of Telkom to grab certain markets. While for returning cash to shareholders, this study prefer stock buyback to dividend as the former provides more flexibility.           Keyword: Corporate Finance, Valuation, Capital Structure, Dividend, Stock Buyback